PEDAGOGICAL APPROACHES TO STIMULATE STUDENTS' CRITICAL AND CREATIVE THINKING - Ecaterina Sarah FRĂSINEANU; Vali ILIE (Universitaria Publishing House, Craiova, 2024)
Our paper presents analyses on the ways of critical and creative learning for students, starting from the premise that, in the learning achieved at this level, there are major changes, determined by the more diverse and demanding social contexts, which requires selection and personalized decision-making skills. Besides the actual learning modalities, there are presented interferences with other demarches specific for academic activities, the risks of criticism, as well as the possible difficulties. Therefore, the value of the study and, at the same time, the hypothesis aimed is to reveal certain concrete aspects of how much and how, some of our students use such paths, based on their usefulness.